Failing at the first hurdle: a profile of coloured children who fail their first year at school. Can they be identified and helped? - Rosen, Eric U (My University, 2014)
Because such a high percentage of coloured children fail Sub A(grade 1) a study was undertaken in the hope that something could be done to remedy this unhappy situation. Although it well known that a major underlying cause of poor school performance can be attributed to poor socio-economic circumstances it was hypothesized that the study, by examining certain biological and environmental factors, would enable one to identify the child at risk of failing. Having done so, a full developmental assessment might then be of help in determining the cfailds areas of weakness and hopefully with the early instituting of appropriate therapy improved academic progress would result. A group of coloured children who had failed in their first school year whilst attending one of 3 schools run by the erstwhile Department of Coloured Education in the vicinity of Coronation Hospital were studied. As controls, children who were the top 5 in each Sub A class at the same schools were enrolled. Variables studied were firstly nutritional status as exemplified by weight and height for age as well as body Iron and Hemoglobin levels. Blood samples were also examined for lead levels.A battery of visual screening tests were administered to both study and control children so that the incidence of visual problems in the study and control groups could be evaluated Psycho-social variables were examined by the adminislration of a questionnaire to the parents of a sample of the children.The questionnnaire, which was drawn up by the researcher, endevoured to cover areas reflecting socio-economic status, family functionality including attitudes to education and expectations for the child, as well as ante-, peri- and postnatal events of the relevant pregnancy.Simultaneously an American questionnaire which concentrated on the home environment and is designed to screen for the child at risk of failing was also completed. Because school teachers are germane to the problem of children being referrred to a developmental asssessment clinic timeously a questionnnaire was developed and administered to the Grades I and 2 teachers at each of the 3 schools used for the study. A small number of children in the study were subjected to a Griffiths Scale of Developmental Assessment test and the results of study subjects and controls were compared. The results of the study showed that nutrition did not seem to play a major role in determining scholastic success at the first hurdle.Visual problems in the first year of school did not affect academic achievement probably because writing on the black board is so large that it negates problems of accommodation. Failure was largely influenced by children commencing school, at too young an age, by lack of stimulation in the home, by a culture of failure as expressed by the poor school record of older siblings and low expectations of parents. Dysfunctional! or disorganised families as epitomised by untidy, messy arid poorly furnished homes also contributed to school failure as did an excessive number of days of absence from school.The American Home Screening questionnaire with an adjusted scoring system appeared to be a useful tool for picking out the child at risk for school failure.The outcome of the Griffiths Scale of Developmental Assessment showed that many of the children had problems which would respond to timeous occupational or speech therapy.It is strongly felt that a compulsory year of pre-school at minimal or no cost to the parents combined with no child being allowed to start formal schooling before the age of 7 years would be useful in improving the academic outcome as well as being cost effective. Children who have problems at the end of the pre-school year should be referred for a developmental assessment.